Implementasi Model Kepemimpinan Transformasional di Pesantren Khozinatul ‘Ulum Blora - Siti Maesaroh; Hamdan Adib; Novan Ardy Wiyani (JIE (Journal of Islamic Education), 2022)
The purpose of this research is to find out the implementation of the transformational leadership model at the Khozinatul 'Ulum Blora Islamic Boarding School by utilizing all the components available in the pesantren. The research method used in this research is descriptive qualitative with data collection techniques used, namely documentation, interviews and observations. The results of this study indicate that transformational leadership is based on several principles, namely: The basic principles in transformational leadership at the Khozinatul Ulum Blora Islamic Boarding School are: first, simplification is shown by the clear vision of the Khozinatul 'Ulum Blora Islamic Boarding School. second, motivation, namely kiai in motivating ustadz and students according to their respective responsibilities. third, facilities, namely providing both physical and academic facilities to students and teachers. fourth, innovation, namely being brave and responsible and open to new things as evidenced by changes in the curriculum and collaboration with various parties on the instructions of the kiai. fifth, mobility, namely by doing a systematic division of labor in accordance with the responsibilities of each component. sixth, determination is proven by evaluation as a form of escort and improvement of activities at the Khozinatul 'Ulum Blora Islamic Boarding School.